Backstepping based real twisting sliding mode control for photovoltaic system - Ullah, Sahib; Malik, Sarmad Majeed; Sun, Yingyun; Numan, Muhammad; Asif, Mansoor; Hu, Junjie; Bodla, Muhammad Kamran (Frontiers in Energy Research, 2023)
Renewable energy sources tied to a utility grid require non-linear control algorithms to provide an efficient and stable output under different operating conditions. The maximum power point tracking (MPPT) approach is necessary for power generation due to non-linear behavior of photovoltaic (PV) power plants. In changing environmental and partial shading conditions, the standard MPPT methods may lead to abnormal results. In this paper, a backstepping based real twisting sliding mode MPPT control is proposed for the PV-battery system where maximum available power is extracted by tracking PV voltage. Moreover, a direct sliding mode control is proposed for battery-integrated buck boost converter for voltage regulation. Reference sliding surface is generated through linear interpolation based on the predicted maximum power point PV voltage. The proposed MPPT strategy is tested against variations of irradiance, temperature, and load. Simulation results highlight superior tracking performance, reduced chattering, and oscillations of this technique over existing models.